Incidental cholecystocolonic fistula in obstructive jaundice - Okidi, Ronald; Ogwang, Martin David; Natumanya, Robert; Mukalazi, Abraham; Kyomuhendo, Tracy; Okello, Tom Richard (Wiley, 2021)
Cholecystocolonic fistula is a rare condition often diagnosed intraoperatively, requiring an adequate set of knowledge and skills to allow safe intraoperative change of prior planned surgery and alleviate significant morbidity.
Keywords: cholecystitis; cholecystocolonic; fistula; jaundice